LAG3-PD-1 Combo Overcome the Disadvantage of Drug Resistance - Wei, Yiming; Li, Zhaoming (Frontiers in Oncology, 2022)
Although PD-1 blockade therapy has been promising in cancer treatment, only 4% (pancreatic cancer) to 70% (melanoma) of patients have a positive response to this blockade therapy, which is one of its important disadvantages. Therefore, it is important to seek out new targets for cancer immunotherapy to improve the overall response rate in patients. Lymphocyte activation gene-3 (LAG-3), an immune checkpoint receptor, is mainly expressed in activated immune cells. LAG-3 maintains the body’s immune homeostasis under physiological conditions while mediating tumour immune escape. Several preclinical and clinical examinations have shown that LAG-3 blockade effectively alleviates the patient’s tolerance to PD-1 immune checkpoint inhibitors. Moreover, the combination of LAG-3 and PD-1 blockade has good clinical efficacy in cancers. Hence, synchronous LAG-3 and PD-1 inhibition may be a potential new strategy for tumour immunotherapy.